2022
DOI: 10.1590/1980-4415v36n72a15
|View full text |Cite
|
Sign up to set email alerts
|

Razonamiento y aprehensión ante una tarea geométrica: análisis de la pertinencia didáctica de una trayectoria de aprendizaje en educación infantil

Abstract: Resumen En esta investigación se analiza la pertinencia didáctica de una trayectoria hipotética de aprendizaje diseñada para fomentar la aprehensión y razonamiento geométrico en aprendices de cuatro y cinco años cuando realizan tareas relacionadas con el concepto de cilindro. Para ello, se ha diseñado e implementado una trayectoria hipotética de aprendizaje en un aula de Educación Infantil con un total de diecinueve infantes. Posteriormente, se ha seleccionado una muestra de cuatro niñas y cuatro niños y se ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
1
0
2
Order By: Relevance
“…Thus, the work described here has shown that this type of practice should be encouraged much more with infant children, because the experience shows that it favors progress in the development of mathematical and critical thinking and helps to build links between scientific and mathematical reasoning, which is consistent with previous findings such as those of Alsina (2020) and Berciano et al (2022). In this sense, this type of teaching-learning in the early childhood education classroom (with a holistic approach to mathematics, science, engineering, art and technology) should be included as part of the examples of good practice in the initial and ongoing training of future early childhood teachers, to help them overcome the gap they have between practical and theoretical knowledge of mathematical argumentation, which has a negative impact when designing practices in this framework, revealing serious difficulties in transferring this knowledge to the education of their future students, children aged three to six years (Broeder & Stokmans, 2009;De Gamboa et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the work described here has shown that this type of practice should be encouraged much more with infant children, because the experience shows that it favors progress in the development of mathematical and critical thinking and helps to build links between scientific and mathematical reasoning, which is consistent with previous findings such as those of Alsina (2020) and Berciano et al (2022). In this sense, this type of teaching-learning in the early childhood education classroom (with a holistic approach to mathematics, science, engineering, art and technology) should be included as part of the examples of good practice in the initial and ongoing training of future early childhood teachers, to help them overcome the gap they have between practical and theoretical knowledge of mathematical argumentation, which has a negative impact when designing practices in this framework, revealing serious difficulties in transferring this knowledge to the education of their future students, children aged three to six years (Broeder & Stokmans, 2009;De Gamboa et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, in this line, it can find works that seek to analyze the impact of the design of the context on the learning process and its reasoning in early childhood education. For example, Berciano et al (2022) in which, based on a teaching experiment designed to work on concepts associated with spatial notions of three-dimensional objects, in this case, the cylinder, analyze the type of geometric reasoning and apprehension that four-and five-year-old children show in a context that seeks to justify their statements and experiment with manipulative material to test their hypotheses. This work shows that the context designed helps them to move to a higher level of geometric reasoning, which helps them to understand in a more meaningful way the relationship between the characteristics of Euclidean space and the Euclidean plane.…”
Section: Mathematical Argumentation In Early Childhood Educationmentioning
confidence: 99%
“…Asimismo, el razonamiento geométrico fomenta la creatividad y la intuición matemática al permitir a los estudiantes visualizar y conceptualizar situaciones espaciales de manera más profunda (Berciano, 2022). Castro (2022) señala que cultivar el razonamiento geométrico en el aula implica no solo la presentación de conceptos y teoremas, sino también la promoción de actividades que desafíen a los estudiantes a pensar de manera crítica y a aplicar sus conocimientos geométricos en contextos diversos.…”
Section: Delio Merma Saico|rolando Oscco Solorzano|josé Gil Huaman Mo...unclassified
“…Razonamiento geométrico de un estudiante universitario activado... conceptos (Haj-Yahya, 2022). Berciano et al (2022) analizaron la importancia y pertinencia de una trayectoria hipotética de aprendizaje para promover el razonamiento geométrico en estudiantes desde las primeras edades (4 y 5 años), en la resolución de problemas en torno al concepto de cilindro.…”
Section: Estado Del Arteunclassified